2005
DOI: 10.1209/epl/i2004-10493-9
|View full text |Cite
|
Sign up to set email alerts
|

Variations on a theme by a singing wineglass

Abstract: A "singing wineglass" is a glass which generates a more or less pure tone when one rubs its rim with a wet finger. The frequency of this tone is lowered when water or wine is poured into the glass. One usually associates this downward frequency shift with an effective mass contributed by the liquid to the vibrating wineglass. We present experimental work and simplified theoretical models to show that this idea requires modifications for a couple of counter-intuitive phenomena.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 9 publications
0
19
1
Order By: Relevance
“…Despite the mathematical equivalence of the internal and external cases, in practice the frequencies were found to be slightly higher for the external cases. It has previously been suggested that the thickness of the glass causes this discrepancy [3], but our solution predicts frequency changes due to thickness to be less than 1%, and this effect is insufficient to explain the discrepancy we observe experimentally, which is closer to 5%. Instead, we suggest that the empirical virtual mass coefficient M differs slightly between internal and external cases, presumably due to slight three-dimensional effects not included in this analysis.…”
contrasting
confidence: 91%
See 1 more Smart Citation
“…Despite the mathematical equivalence of the internal and external cases, in practice the frequencies were found to be slightly higher for the external cases. It has previously been suggested that the thickness of the glass causes this discrepancy [3], but our solution predicts frequency changes due to thickness to be less than 1%, and this effect is insufficient to explain the discrepancy we observe experimentally, which is closer to 5%. Instead, we suggest that the empirical virtual mass coefficient M differs slightly between internal and external cases, presumably due to slight three-dimensional effects not included in this analysis.…”
contrasting
confidence: 91%
“…Building upon Rayleigh's Theory of Sound [1], French [2] used energy conservation to develop the first mathematical model of a glass harp. Since then, researchers have confirmed the French model through experiment [3,5,6] and explored some details of the dynamics at the finger-glass interface [7,8]. Some work has also been done to quantify the pitches that result from changing the distribution of water in and around the glass [3,6].…”
mentioning
confidence: 99%
“…Three cumulative distributions of ejected droplet sizes are presented on Fig. 11a for the bowls Tibet 1, 3 and 4 resonating in their fundamental deformation modes (2,0). Assuming that these distributions are Gaussian, appropriate fits to the cumulative distribution functions yield the parameters of the Gaussian distribution functions plotted in the inset of Fig.…”
Section: Surface Fracturementioning
confidence: 99%
“…Despite their commonplace ubiquity, current theoretical understanding of their vibrational characteristics is incomplete. Existing literature [22,23,[27][28][29][30] typically assumes specific forms and coefficients for dynamical equations, fluid damping is neglected, or system geometry is vastly simplified, compromising predictive power; more general models typically rely on finite-element computations offering limited tractability and insight. We seek to contribute in closing this lacuna in the current paper.…”
Section: Introductionmentioning
confidence: 99%